Is the eye lens method of age estimation reliable in voles? - Jánová Eva; Nesvadbová Jiřina; Tkadlec Emil
We examined the reliability of laboratory-derived calibration curves for age determination of field individuals of the common vole, Microtus arvalis. The sex-specific calibration curves for age determination based on the relationship between eye lens mass and age derived in the laboratory were applied to a live-trapped field population of common vole. When comparing the individual’s age to the length of its trapping history, we found a slight tendency for underestimation of real age. These errors were observed slightly more in females than in males and in individuals captured over a longer time. This could mean that growth rates in captive animals, especially older ones, and in females are greater than those from the field. The month of first trapping has no effect on the presence of the error. We suggest that, in population studies with a special concern for ageing individuals over the whole life span, other methods should be examined, such as those measuring insoluble eye lens proteins or calibration curves based on more than one predictor.